Clouds and light : impressionism in Holland - Philipp, Michael, 1962-; Westheider, Ortrud; Zamani, Daniel; Museum Barberini (Potsdam, Germany) (Munich, Germany : Prestel, 2023)
"Impressionism may have originated in France, but artists in late 19th- and early 20th-century Netherlands quickly made it their own. The genre's vibrant colors and focus on light and atmosphere were a perfect complement to the country's groundbreaking traditions of landscape painting and realism. This exhibition catalog brings together hundreds of works by nearly forty artists including Johan Barthold Jongkind, Vincent van Gogh, Jacoba van Heemskerck, and Piet Mondrian. It traces the birth of the Hague School, whose practitioners captured the changing moods of light in the coastline's vast, grey skies. And it explores the Amsterdam Impressionists, whose cityscapes offered realistic images of modern life. Alongside vibrant reproductions of masterworks, a series of lively essays explore a diverse array of topics, including Dutch landscape painting within an international context; Dutch artist settlements and communities; and iconography in Dutch impressionism"
Atmosphere and feeling : the painting of Dutch light / Frouke van Dijke -- Art and friendship : the artists' associations and villages of Dutch Impressionism / Jeroen Kapelle -- Tomorrow's aesthetic : French artistic notions and Dutch Impressionism / Mayken Jonkman -- Making an impression : the art market and exhibitions of contemporary Dutch art, 1850-1910 / Renske Cohen Tervaert -- Devotees of nature : nineteenth-century Dutch landscape painting from an international perspective / Renske Suijver -- Monumental mills : the iconography of a Dutch symbol, 1850-1920 / Michael Philipp --Light and shadow under trees : Painting in nature / Quirine van der Meer Mohr -- Flat Meadows, open skies : The Character of the landscape / Michael Philipp -- Boats on a low horizon : Costal Motifs / Jacqueline Hartwig -- The energry of modernity : Images of the City / Lucien Midavaine -- Holiday at the sea : Jacqueline hartwig -- Enclosed landscapes : Garden scenes / Lucien Midavaine --Calculated effects of light : The Pointillist phase / Jacqueline Hartwig -- Brilliant Hues : The Intensification of color / Marijn Geist -- Free colors, free forms : Sterre Barentsen -- Appendix.
Catalog of an exhibition held at the Museum Barberini, Potsdam, July 8-October 22, 2023--Colophon.
Includes bibliographical references (pages 304-307).
Keywords: Painting, Dutch -- 19th century -- Exhibitions; Impressionism (Art) -- Netherlands -- Exhibitions; Peinture néerlandaise -- 19e siècle -- Expositions; Impressionnisme (Art) -- Pays-Bas -- Expositions; Painting, Dutch; Impressionism (Art); Netherlands; 19th century; exhibition catalogs; Exhibition catalogs; Biographies; Exhibition catalogs; Art criticism; Catalogues d'exposition.; Critiques d'art.